Noise properties of contactless integrated photonic probes on silicon waveguides - Wang, Zhao; Zhang, Ziyu; Zou, Kai; Meng, Yun; Liu, Haiyi; Hu, Xiaolong (Applied optics. Optical technology and biomedical optics, 2023)
Contactless integrated photonic probes (CLIPPs) have been used as on-chip power monitors with minimum perturbations to optical modes. In this work, we present the experimental measurements and analysis of the noise properties of these types of devices integrated with silicon waveguides. We focus on the study of how circuitry parameters, including the gain of the trans-impedance amplifier, lock-in bandwidth, and amplitude and frequency of the bias voltage, affect the noise properties. Finally, we establish a circuit model and use the Simulation Program with Integrated Circuit Emphasis to model and simulate the noise properties of these devices. Our analysis shows that the thermal noise of the CLIPPs and electrical noise of the trans-impedance amplifier are the dominant sources of noise.